Efficacy of two vaccine formulations against contagious bovine pleuropneumonia (CBPP) in Kenyan indigenous cattle - Nkando, I.; Ndinda, J.; Kuria, J.; Naessens, Jan; Mbithi, F.; Schnier, C.; Gicheru, M.; McKeever, Declan J.; Wesonga, H.O. (Elsevier, 2012)
A live, attenuated vaccine is currently the only viable option to control of CBPP in Africa. It has been suggested that simple modifications to current vaccines and protocols might improve efficacy in the field. In this report we compared the current vaccine formulation with a buffered preparation that maintains Mycoplasma viability at ambient temperature for a longer time. Groups of animals were vaccinated with the two formulations and compared with non vaccinated groups. Half of the animals in each group were challenged 3months post vaccination, the other half after 16months. Protection levels were measured using the pathology index, calculated from post mortem scores of lesions from animals killed during the course of clinical disease. In the challenge at 3months post vaccination, the protection levels were 52% and 77% for the modified and current vaccine preparations, respectively. At 16months post vaccination, the protection levels were 56% and 62% for the modified and current vaccine preparations, respectively. These findings indicate that there are no differences in protection levels between the two vaccines. Because of its longer half life after reconstitution, the modified vaccine might be preferred in field situations where the reconstituted vaccine is likely not to be administered immediately.